2012
DOI: 10.3171/2011.12.peds11169
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an injury prevention program on teenagers' knowledge and attitudes: results of the Pense Bem–Caxias do Sul Project

Abstract: Object Trauma is the leading cause of mortality and morbidity in children, young people, and working-age adults. Because of the high incidence of intentional and unintentional injuries in young people, it is necessary to implement injury-prevention programs and measure the efficacy of these initiatives. The authors evaluated the effectiveness of an injury-prevention program in high school students in a city in southern Brazil. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 17 publications
0
13
0
1
Order By: Relevance
“…Of these, 60 full texts were retrieved and further screened, and 35 studies were finally included ( Figure 1 ). Of these 35 studies, 7 were before–after studies [24] , [25] , [26] , [27] , [28] , [29] , [30] and 28 were controlled trials [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] . Of the trials included in this review, 19 were adequately randomized [32] , [33] , [37] , [38] , [39] , [40] , [41] , [44] , [45] , [46] , [47] , [48] , [50] , [53] , [54] , [55] , [56] , [57] , [58] , and all controlled trials had appropriate control groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, 60 full texts were retrieved and further screened, and 35 studies were finally included ( Figure 1 ). Of these 35 studies, 7 were before–after studies [24] , [25] , [26] , [27] , [28] , [29] , [30] and 28 were controlled trials [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] . Of the trials included in this review, 19 were adequately randomized [32] , [33] , [37] , [38] , [39] , [40] , [41] , [44] , [45] , [46] , [47] , [48] , [50] , [53] , [54] , [55] , [56] , [57] , [58] , and all controlled trials had appropriate control groups.…”
Section: Resultsmentioning
confidence: 99%
“…With the exception of Brazil, all included studies were conducted in HICs including USA, Canada, Australia, Switzerland, Sweden, and Norway. Eleven of the included studies were conducted in a local school [24] , [27] , [28] , [30] , [32] , [33] , [34] , [37] , [38] , [39] , [41] , [44] , [46] , [51] , 19 were conducted in community settings [25] , [26] , [29] , [35] , [36] , [40] , [42] , [43] , [45] , [48] , [49] , [50] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , and the remaining studies were conducted in hospital settings [31] .…”
Section: Resultsmentioning
confidence: 99%
“…Several studies demonstrated the effectiveness of educational interventions (e.g., concussion videos, lectures, web-based resources, etc.) which helped increase concussion knowledge of athletes (Cusimano, Chipman, Donnelly, & Hutchison, 2014;Glang et al, 2015;Miyashita, Timpson, Frye, & Gloeckner, 2013), coaches (Covassin, et al, 2012), parents (Glang et al, 2015), and non-athlete students (Bagley et al, 2012;Falavigna et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…('Think Well!') Project, which is a partnership of the Brazilian Society of Neurosurgery and the Ministry of Health that promotes public information campaigns for the prevention of head and spine trauma 27,28 . According to recent data and the results of the present study, significant benefits may be obtained by directing efforts at solving severe housing problems that are very common in large Brazilian cities.…”
Section: Discussionmentioning
confidence: 99%